Effects of NaCl and MTGase on printability and gelling properties of extrusion-based 3D printed white croaker (Argyrosomus argentatus) surimi. (15th July 2022) - Cao, Feifan; Chen, Ruiyang; Li, Yang; Han, Rong; Li, Feng; Shi, Hu; Jiao, Yang
Abstract: Surimi has been explored as a promising 3D printed ingredient, but its rheological properties need to be identified for printing accuracy and gelling properties improvement. This study investigated the printability of white croaker surimi mixtures with NaCl and microbial transglutaminase (MTGase) in an extrusion-based 3D printing process and their gel forming characteristics after thermal treatment. The surimi mixture with different levels of NaCl (5–40 g/kg) and MTGase (0–4.0 g/kg) behaved as Herschel-Bulkley fluid. The rheological properties and printing performance screened out the appropriate amount of additive (20 g/kg NaCl and 2.0 g/kg MTGase) suitable for 3D printing. Compared the conventionally prepared surimi gels, 3D printed surimi gels with 70% infilled density had similar or even higher water holding capacity and gel strength, but lower L and whiteness values significantly ( p  < 0.05) because of the porous structure created by 3D printing. The addition of NaCl and MTGase had significant effect on the 3D printability of surimi, and the mechanical properties of 3D printed surimi gels were comparable to the conventionally prepared ones. Highlights: White croaker surimi mixture is a Herschel-Bulkley fluid. Microbial transglutaminase in surimi enhances G′ and G″, but NaCl does the opposite. Surimi with 20 g/kg NaCl and 2.0 g/kg MTGase has the optimum printing accuracy. 3D printing improves water holding capacity of surimi gels.